Association of park drinking water source characteristics and water intake in San Francisco Bay Area parks. Issue 1 (14th February 2022) - Ezennia, Jeffery; Schmidt, Laura A.; Blacker, Lauren S.; Vargas, Roberto A.; McCulloch, Charles E.; Patel, Anisha I.
Abstract: Over half of U.S. adults visit parks regularly. Thus, it is important to understand how park drinking water sources affect visitors' water consumption. In this cross-sectional study of 30 San Francisco Bay Area parks, 4 day-long direct observations of visitors' drinking water and other beverages were conducted, along with audits of sugar-sweetened beverage access and drinking water source conditions, including flow, appeal, and obstructions. Outcomes were log-transformed to account for skewness, and results were analyzed using mixed-effects regression models to account for matching and clustering by park and observation day. A greater proportion of water sources in low-income parks were unappealing (57.14 vs. 25.00%, P = 0.01) or in a poor condition (69.70 vs. 43.24%, P = 0.03). A lower proportion of visitors drank water from park fountains that were unappealing (−31%), had poor flow (−22%), or had obstructions (−58%) than those without these conditions. Although only obstructions to the source and water intake were significantly related after adjustment, we observed important effects on water intake by water source appeal and flow. As park water source conditions contribute to water intake, cities should consider installing appealing, functional, and easy to access water sources in parks, particularly those in lower-income neighborhoods. HIGHLIGHTS: This study is the first to assess how drinking water source conditions influence water intake in park settings. Water sources were in poorer condition in parks located in lower-income neighborhoods. Water source conditions influence water intake in park settings. Water sources were in poorer condition in parks located in lower-income neighborhoods.